2016
DOI: 10.1080/14786419.2016.1154058
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and chemical variability in volatile oils of aerial parts of Morinda morindoides

Abstract: Morinda morindoides is an important Liberian traditional medicine for the treatment of malaria, fever, worms etc. The plant was subjected to integrated approaches including phytochemical screening and gas chromatography mass spectrometry (GC-MS) analyses. Phytochemical investigation of the powdered plant revealed the presence of phenolics, tannins, flavonoids, saponins, terpenes, steroidal compounds and volatile oil. Steam distillation followed by GC-MS resulted in the identification of 47 volatiles in its aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…While the literature data highlight on the presence of saponins (Cimanga et al, 2010), terpenes, steroids, tannins, and anthraquinones (Kiazolu et al, 2016) and extensive phytochemical studies on this Morinda species have resulted in the isolation of some compounds such as flavonoids (Cimanga et al, 2006, 2008), iridoids (Cimanga et al, 2003, 2006a; Tamura et al, 2010), and anthraquinones (Cimanga et al, 2008). Several studies have highlighted on the biological activities of M. morindoides related to its traditional use, which include antimalarial (Cimanga et al, 2008; Onabanjo, 1983; Tona et al, 2001), antioxidant (Cimanga et al, 1999), antidiarrheal (Meite et al, 2009), antiamebic (Cimanga et al, 2006b), and anticomplementary activity (Cimanga et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While the literature data highlight on the presence of saponins (Cimanga et al, 2010), terpenes, steroids, tannins, and anthraquinones (Kiazolu et al, 2016) and extensive phytochemical studies on this Morinda species have resulted in the isolation of some compounds such as flavonoids (Cimanga et al, 2006, 2008), iridoids (Cimanga et al, 2003, 2006a; Tamura et al, 2010), and anthraquinones (Cimanga et al, 2008). Several studies have highlighted on the biological activities of M. morindoides related to its traditional use, which include antimalarial (Cimanga et al, 2008; Onabanjo, 1983; Tona et al, 2001), antioxidant (Cimanga et al, 1999), antidiarrheal (Meite et al, 2009), antiamebic (Cimanga et al, 2006b), and anticomplementary activity (Cimanga et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The interspecific variability of essential oils produces different chemotypes by a combination of genetic and environmental factors [83] and may contribute to the diversification of ecological interactions between plants and insects [84, 85].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, plants grow rapidly and produce better biomass yields in less stressful environments. Many studies have revealed that the constitution and concentration of phenolic compounds and metabolites in medicinal plants, including Perilla, are largely influenced by various factors such as growth season, environment, light intensity or quality, cultivation methodology, phenological stage, nutrient level, and harvest time (Saeb and Gholamrezaee, 2012;Yoshimatsu, 2012;Chauhan et al, 2013;Selmar and Kleinwachter, 2013;Ha et al, 2012;Kiazolu et al, 2016;Lu et al, 2017;Kim et al, 2017;Umakanta and Oba, 2018). Moreover, Hikosaka et al (2017) reported that greenhouse cultivation is an effective method for the steady production of medicinal plants because environmental conditions can be controlled, and furthermore, safer medicinal plants are produced with the use of agrochemicals.…”
Section: Introductionmentioning
confidence: 99%